DISTRIBUTION OF ORGANIC MATTER IN SEDIMENTS OF SUNGAI MESJIDESTUARY, PURNAMA MARINE STATION, DUMAI CITY, RIAU PROVINCE - Pranata, Eryc; Rifardi, Rifardi; Musrifin, Musrifin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACK This research was conducted from February to March 2019 which is located in the estuary waters of the Sungai MesjidPurnama Marine Station, Dumai City, Riau Province. Data analysis of organic matter was carried out at the Physical Oceanography Laboratory of Marine SciencesDepartment, Faculty of Fisheries and Marine, University Of Riau. This study aims to determine the distribution of organic matter in sediments in estuary areas that are affected by 2 water masses,currents and semidiurnal tidal analysis distribution of organic matter showed that the distribution of organic matter content at low tide ranged from 4.90 to 16.50 %. The results show that the waterflow of Sungai Mesjid toPurnama coast there are mangrove ecosystems.During tidal events currents from Sungai Mesjid meet with the mass of water from the RupatStrait. Purnama. Key words :Organic Matter, Sungai Mesjid,Mangrove, Currents, Tides